2014
DOI: 10.1080/15389588.2014.935939
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption Among Drivers in Curitiba, Brazil

Abstract: This study, conducted on public roads in Curitiba, shows a noticeable proportion of drivers voluntarily self-reporting drinking and driving. However, a smaller percentage was confirmed to have positive blood alcohol content, likely due to the high breathalyzer refusal rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
2
7
0
1
Order By: Relevance
“…Confirming the findings of the existing literature, 10,27 men committed more violations, especially speeding 2 and talking on the phone. 2 Studies suggest that women perceive a greater amount of risk involved in committing a violation, while men feel more capable of driving and are more defiant regarding traffic laws, and thus obey such laws selectively in a situation-dependent manner.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Confirming the findings of the existing literature, 10,27 men committed more violations, especially speeding 2 and talking on the phone. 2 Studies suggest that women perceive a greater amount of risk involved in committing a violation, while men feel more capable of driving and are more defiant regarding traffic laws, and thus obey such laws selectively in a situation-dependent manner.…”
Section: Discussionsupporting
confidence: 78%
“…Studies show a high prevalence of drinking and driving among Brazilian drivers due to cultural differences regarding the use of alcohol and a low perception of punishment. 9,10 Schimitz et al 20 warn that the lack of effective enforcement of traffic legislation results in a feeling of impunity and contributes to the maintenance of high-risk behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, driving whist above the legal BAC limit has declined significantly to 2% in the US (Kelley-Baker et al, 2012). In Curitiba, (Brazil), a roadside breath test among truck drivers revealed that 2.7% drivers had detectable alcohol in their breath tests (Aguilera et al, 2014) whilst 0.4% tested positive in Norway among whom only 0.2% were above the legal limit of 0.02% (Gjerde et al, 2012). Pechansky and colleagues (2012) also established that less than 5% of motorists in a roadside breathalyser studies in Brazilian capitals had detectable alcohol in their breath.…”
Section: Introductionmentioning
confidence: 99%